Styles, Classification, and Development of Transportation Street Networks in Ranya City between 1957 and2024 (Raparin Journal of Humanities (RJH), 2025)
Transportation street networks are na important part of urban infrastructure which  plays  a great role in enabling investment and allowing residents to carry out their daily activities. These networks must be developed in ways that meet the population's evolving needs, ensure safety, support urban expansion, and contribute to a city's modern and organized appearance. Historically, in Ranya City, the street network was basic, unplanned, and untidy, which designed only to meet the minimal demands of a smaller population. Over time, as the city grew and its population expanded, the street network evolved through various morphological stages. This research examines the development and transformation of Ranya’s street network over the years, focusing on its classification and current condition. The study aims to evaluate the current transportation street network and highlight its importance for future master planning. It also identifies existing issues and compares Ranya’s networks to international standards and those in developed countries. The findings reveal that the total length of streets increased from 16.69 km in 1957 to 114.09 km in 2024 which represents a sevenfold increase since the city's earliest developmental stage. This demonstrates that the development of transportation street networks is a cornerstone of urban economic growth and civilization.